PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT. POS INDONESIA (PERSERO) SANGATTA - Suyatin3, Anik Rofiah1 Theresia Militina2 (EKONOMIA, 2016)
The main objective of this reseach is to analyze the effect of service quality to customer satisfaction at PT. Pos Indonesia (PERSERO) Sangatta.Model analysis used to determine to effect of service quality on customer satisfaction is linear multiple regression method.The analysis and discussion shows that the variable of service quality which tangible, reliability, responsiveness, assurance, and empathy together (simultane) significant effect on the post in the customer satisfaction PT. Pos Indonesia (PERSERO) Sangatta with F count in 9,368 with points of significant (P Value) is 0,000<0,05, where tangible effect not significant on customer satisfaction with the significant value (P Value) is 0,106>0,05. Realiability effect on significant customer satisfaction with the significant value (P Value) is 0,012<0,05. Responsiveness effect not significant on customer satisfaction with significant value (P Value) is 0,189>0,05. Assurance effect on significant customer satisfaction with the significant value (P Value) is 0,045<0,05. Empathy effect not significant on customer satisfaction with significant value (P Value) is 0,241>0,05. As we know that the correlation coefficient value is 0,540 it means that there are strong correlation and positive between independent variable with dependent variable while determine coefficient product is 0,291 or 29,1% it means the customer satisfaction 29,1% effect by independent variable is tangible (X1), reliability (X2), responsiveness (X3), assurance (X4), and empathy (X5) while remine is 70,9% explained by the other factor is not search in this research.